Correlation of post-operative albumin level to the clinical outcome in patients undergoing abdominal (intra-peritoneal) surgery - P. J., Sriram Prabhu; Patankar, Shilpa (International Surgery Journal, 2022)
Background: Surgical interventions have become part and parcel of an individual’s life. The average number of surgeries that a person undergoes in their lifetime is 9.2 (3.4 inpatient operations, 2.6 outpatient operations, and 3.2 non-operating room invasive procedures). So it is important to make sure that the patient undergoes surgery smoothly and gets out of hospital well at early days. There are many factors that help to predict the outcome post surgeries, in this study we have used albumin (pre and post op) and its difference for predicting the clinical outcome. Methods: 80 patients who are undergoing abdominal (intra-peritoneal) surgeries from October 2019 to December 2020 was studied. Serum albumin was estimated by Randox albumin assay method. Serum albumin level was obtained pre-operatively, post-op after 6 hours and on POD-1 and their difference is found and compared with clinical outcome using Clavien-Dindo classification. Results: It was observed that 81.5% (22 out of 27) of patients with albumin drop more than 10% by 6 hours post operatively are likely to develop complications of surgery. It was observed that 89% (16 out of 18) of patients with albumin drop more than 15% by POD1 are likely to develop complications of surgery. Conclusions: In our study raised serum albumin drop post-operatively was associated with complications and so it can be concluded that serum albumin may be used as a marker for predicting the clinical outcome of the patients undergoing surgery.